Effects of feedback, gender, and explanatory style on mood, and performance in collegiate swimmers - Marsden, K.; Garske, J. P.; Ogles, B. M. (Medicine & Science in Sports & Exercise, 1993)
Swimmers performed their best event worse after receiving false negative feedback than after accurate feedback. This occurred independent of sex or pessimism or optimism in the swimmer. Implication: A coach's reaction to a swim can affect the next performance. If what the coach says is contrary to the swimmer's assessment of performance (inaccurate feedback) a subsequent swim is likely to be worse. Simply put, realistic positive feedback is likely to have the best effect on swimmers.